EFEITO DO TRATAMENTO DE SEMENTES DE AMENDOIM NO STAND DE GERMINAÇÃO - Fancelli, Maria Isabel; Kimati, H. (REVISTA DE AGRICULTURA, 2015)
EFEITO DO TRATAMENTO DE SEMENTES DE AMENDOIM NO STAND DE GERMINAÇÃO